2017
DOI: 10.1073/pnas.1711345114
|View full text |Cite
|
Sign up to set email alerts
|

SIRPα+dendritic cells regulate homeostasis of fibroblastic reticular cells via TNF receptor ligands in the adult spleen

Abstract: In secondary lymphoid organs, development and homeostasis of stromal cells such as podoplanin (Pdpn)-positive fibroblastic reticular cells (FRCs) are regulated by hematopoietic cells, but the cellular and molecular mechanisms of such regulation have remained unclear. Here we show that ablation of either signal regulatory protein α (SIRPα), an Ig superfamily protein, or its ligand CD47 in conventional dendritic cells (cDCs) markedly reduced the number of CD4 cDCs as well as that of Pdpn FRCs and T cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 44 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…Signal regulatory protein α mutant mice, which express a mutant form of SIRPα that lacks most of the cytoplasmic region and thus fail to bind Shp1 and Shp2, manifested mild anemia associated with a short lifetime of RBCs as a result of increased phagocytotic activity of splenic macrophages against RBCs, suggesting the importance of SIRPα for both the lifespan of RBCs and their number in the circulation. In addition, DC‐specific SIRPα knockout mice showed a reduced number of DCs, as well as of fibroblastic reticular cells, a subset of stromal cells, in the spleen . Moreover, SIRPα mutant mice, as well as CD47‐deficient mice, were resistant to the development of autoimmune animal models, such as experimental autoimmune encephalomyelitis, suggesting that the interaction of SIRPα with CD47 is involved in the development of autoimmune diseases.…”
Section: Signal Regulatory Protein α and Its Biological Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal regulatory protein α mutant mice, which express a mutant form of SIRPα that lacks most of the cytoplasmic region and thus fail to bind Shp1 and Shp2, manifested mild anemia associated with a short lifetime of RBCs as a result of increased phagocytotic activity of splenic macrophages against RBCs, suggesting the importance of SIRPα for both the lifespan of RBCs and their number in the circulation. In addition, DC‐specific SIRPα knockout mice showed a reduced number of DCs, as well as of fibroblastic reticular cells, a subset of stromal cells, in the spleen . Moreover, SIRPα mutant mice, as well as CD47‐deficient mice, were resistant to the development of autoimmune animal models, such as experimental autoimmune encephalomyelitis, suggesting that the interaction of SIRPα with CD47 is involved in the development of autoimmune diseases.…”
Section: Signal Regulatory Protein α and Its Biological Functionsmentioning
confidence: 99%
“…In addition, DC-specific SIRPα knockout mice showed a reduced number of DCs, as well as of fibroblastic reticular cells, a subset of stromal cells, in the spleen. 27 Moreover, SIRPα mutant mice, as well as CD47-deficient mice, were resistant to the development of autoimmune animal models, such as experimental autoimmune encephalomyelitis, 28,29 suggesting that the interaction of SIRPα with CD47 is involved in the development of autoimmune diseases. SIRPα and CD47 are also thought to play a role in the regulation of central nervous system functions.…”
Section: Its Biological Functionsmentioning
confidence: 99%
“…This process is coordinated by TGF-β and is necessary for the differentiation of FRCs [150]. Once Peyer's patches are fully developed and populated, leukocytes help to maintain stromal cell differentiation; B cells are particularly important for the maintenance of FDCs [151], whereas DCs are important for the maintenance of FRCs [152]. Finally, the interactions between the microbiota and epithelial cells are arguably as important as the interactions between leukocytes and stromal cells for the maintenance of Peyer's patches [153], particularly for the differentiation of M cells [154], the expression of epithelial chemokines, and the organization of the dome region [129].…”
Section: The Reciprocal Interactions Between Ltαβexpressing Lti Cellsmentioning
confidence: 99%
“…DCs also express lymphotoxin α 1 β 2 and promote the survival of FRCs through its interaction with LTβR on FRCs . We have recently shown that CD4 + conventional DCs (cDCs) regulate the steady‐state homeostasis of FRCs in the adult mouse spleen via the production of TNF receptor (TNFR) ligands such as TNF‐α .…”
Section: Introductionmentioning
confidence: 99%
“…It possesses three immunoglobulin‐like domains in its extracellular region and an immunoreceptor tyrosine‐based inhibition motif that binds the protein tyrosine phosphatases Shp1 and Shp2 in its intracellular region . We have recently demonstrated that SIRPα expressed on cDCs is indispensable for the homeostatic regulation of splenic FRCs . However, it has remained unclear whether SIRPα + DCs participate in the development of FRCs in peripheral LNs (pLNs).…”
Section: Introductionmentioning
confidence: 99%